Tingkat Prevalensi Escherichia Coli Dalam Daging Ayam Beku yang Dilalulintaskan Melalui Pelabuhan Penyeberangan Merak - G. I. Dewantoro; M. W. Adiningsih; T. Purnawarman; T. Sunartatie; U. Afiff (Jurnal Ilmu Pertanian Indonesia, 2009)
The aimed of this study was to determine prevalence of Escherichia coli in frozen chicken meat transported through Merak port. The samples were taken from DKI Jakarta (16 samples), Bekasi (11 samples), Bogor (8 samples), and Serang (18 samples). The average number of E. coli in frozen chicken meat from DKI Jakarta was 0.43x101±0.28x101 MPN/g, Bekasi was 10.4x101 ±33.04x101 MPN/g, Bogor was 0.28x101 ±0.23x101 MPN/g, and Serang was 6.72x101±25.79x101 MPN/g. Based on the result of ANOVA, the four areas had no significance in diferrence (p>0.05). The conclusion of this study showed that the average number of E. coli from Bekasi and Serang were over the maximum limit of microbial contamination as permitted by SNI 01-7388-2009 (1x101 MPN/g), whereas DKI Jakarta and Bogor were under the maximum limit. The prevalence of E. coli in frozen chicken meat from DKI Jakarta was 31.25°/o, Bekasi 31.25°/o, Bogor 27.27°/o, and Serang was 27.78°/o.